Nonconventional thermal states of interacting bosonic oligomers - Amichay Vardi; Alba Ramos; Tsampikos Kottos (Physical Review Research)
There has recently been a growing effort to understand the physics and intricate dynamics of many-body and many-state (multimode) interacting bosonic systems in a comprehensive manner. For instance, in photonics, nonlinear multimode fibers are being intensely investigated nowadays due to their promise for ultrahigh-bandwidth and high-power capabilities. Similar prospects are being pursued in connection with magnon Bose-Einstein (BE) condensates, and ultracold atoms in periodic lattices for room-temperature quantum devices and quantum computation, respectively. While it is practically impossible to monitor the phase space of such complex systems (classically or quantum mechanically), thermodynamics has succeeded in predicting their thermal state: the Rayleigh-Jeans (RJ) distribution for classical fields and the BE distribution for quantum systems. These distributions are monotonic and promote either the ground state or the most excited mode. Here, we demonstrate the possibility to advance the participation of other modes in the thermal state of bosonic oligomers. The resulting nonmonotonic modal occupancies are described by a microcanonical treatment, while they deviate drastically from the RJ/BE predictions of canonical and grand-canonical ensembles. Our results provide a paradigm of ensemble equivalence violation and can be used for designing the shape of thermal states.